Therapists’ and Patients’ Perspectives on Therapeutic Dynamics Leading to Therapy Failure in Forensic Addiction Treatment - Querengässer, Jan; Langenstück, Lena; Hoffmann, Klaus (Frontiers in Psychiatry, 2019)
Background: Among drug- or alcohol-addicted offenders under forensic treatment, therapy failure is a potent predictor of substance-related re-delinquency. Given this evidence, high drop-out rates pose a major problem in forensic addiction treatment in Germany. Legal preconditions for a premature discharge due to therapy failure are defined, and behavioral correlates are well described, but the precedent dynamics between patients and therapists have rarely been analyzed. The present study intended to shed light upon the subjective perception of the treatment course prior to therapy failure. Methods: Applying parallel questionnaires and structured interviews, patients' and therapists' perspectives on perceived reasons for therapy failure and (self-)criticism were retrospectively investigated and compared to each other on a dyadic level. Following this predominantly qualitative and explorative approach, the examination of 32 dyads could be realized; 13 patients with regular (i.e., successful) therapy termination served as controls. All patients had been treated within two specialized forensic addiction hospitals in the German federal state of Baden-Württemberg and were assessed shortly before discharge took place. Results: As expected, patients' and therapists' perspectives differed largely on perceived reasons for failure and on (self-)criticism. In most cases, they appeared to have very different views on what happened during treatment and why therapy eventually failed. The analysis of patients’ narratives regarding how to explain the negative treatment course confirmed pre-assumptions on predominantly negative feelings and attitudes towards the clinic. The precedent dynamics of therapy failure were shown to be highly individual. However, despite varying notably, a cluster analysis revealed that they seemed to follow "typical patterns" that could partially be linked to patients' characteristics. Conclusions: A better understanding of treatment dynamics during forensic addiction therapy is a prerequisite for the avoidance of therapy failure with negative effects on re-delinquency. It seems that the incapacity to establish a common frame of reference for assessing the therapy process could be one of the major reasons why treatment dynamics take on a life of their own towards a disruption of the therapeutic relationship, leading to therapy failure. The knowledge of "typical" risk patterns towards therapy failure could facilitate early therapeutic measures.